Ingested Polystyrene Micro-Nanoplastics Increase the Absorption of Co-Ingested Arsenic and Boscalid in an In Vitro Triculture Small Intestinal Epithelium Model - Davood Kharaghani; Glen M. DeLoid; Trung Huu Bui; Nubia Zuverza-Mena; Carlos Tamez; Craig Musante; Jason C. White; Philip Demokritou (Microplastics)
Micro-nano plastics (MNPs) are emerging environmental and food contaminants that are raising serious health concerns. Due to the polycontamination of the food web with environmental pollutants (EPs), and now MNPs, the co-ingestion of EPs and MNPs is likely to occur, and the potential synergistic effects of such co-ingestions are completely unstudied. In this study, we therefore sought to determine the effects of the two model EPs, arsenic and boscalid, on the uptake and toxicity of two model MNPs, 25 and 1000 nm polystyrene (PS-25 and PS-1000), and vice versa, employing a triculture small intestinal epithelium model combined with simulated digestion. In 24 h triculture exposures, neither MNPs, EPs, nor MNPs + EPs caused significant toxicity. The presence of PS-25 significantly increased arsenic uptake (from 0.0 to 5.8%, p < 0.001) and translocation (from 5.2 to 9.8%, p < 0.05) but had no effect on boscalid uptake or translocation, whereas PS-1000 had no effect on the uptake or translocation of either EP. The uptake of both PS MNPs was also increased by EPs, rising from 10.6 to 19.5% (p < 0.01) for PS-25 and from 4.8 to 8.5% (p < 0.01) for PS-1000. These findings highlight the need for further studies to assess MNP-EP interactions and possible synergistic adverse health impacts.